PROSPEK PENGEMBANGAN INDUSTRI BAHAN GALIAN GOLONGAN C (PASIR DAN BATU KERIKIL) DI KABUPATEN KAMPAR (Studi Kasus Desa Pulau Permai Kecamatan Tambang) - Davitra Hamid; Jahrizal '; Rahmat Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
In districts Tambang, the village of PulauPermai is an area that is located in the district of Kampar region traversed the river Kampar. Residents take advantage of potential economic resources contained in the river and create jobs. Types of non-farm jobs that are often encountered in the mining districts are berburuh, including construction workers, miners excavated material class c, brick industrial workers and agricultural laborers.Mineral mining group C has a strategic role and function in regional economic development activities. In addition to having access to important for the sustainability of the industrial sector manukfaktur and construction, mining activity is at least one access can be a livelihood for the people who low income. The purpose of this study was to determine the development prospects of industrial minerals C sand-gravel in the village of PulauPermai Kampar District Kampar Regency. The data were analyzed qualitatively and quantitatively. Qualitative data analysis was conductedto determine the characteristics of the minerals industry C. Quantitative data was conducted to determine the state of financial companies such as Net B / C Ratio, NPV, and IRR. From the results of the aspects examined in this study that is based on market and marketing aspects, technical aspects and financial aspects Enterprises Quarrying C Mining sand and stone in the village of PulauPermai Kampar District Kampar Regency viable, while based on management aspects,legal aspects, and aspects the environment is not considered feasible.Keywords: Prospect, Excavated and Materials Industry Group C.